Rights-Based Education in Nepal: Existing Status and Challenges - Jnawali, Damodar (The Third Pole: Journal of Geography Education, 2014)
This paper is an attempt to deal with the issues and challenges of rights-based education in Nepal with specific reference to minority and disadvantaged group children at school level. Data and information are from three year formative research activities completed under the commission of CERID, TU, Nepal. Discourses of various stakeholders were solicited in order to elicit information. Students’ interactions, class observations, focus group discussions with people in local communities and district level officials, and district as well as national level workshops were conducted in order to elicit information for the study. The findings of the study indicate that the provisions for rights-based education are still inefficient in order to achieve the EFA goals. In spite of the attempts made by community, government, NGOs and INGOs, there are many challenges to provide rights-based education to those who are socially excluded. DOI: http://dx.doi.org/10.3126/ttp.v8i0.11506 The Third Pole Vol. 8-10, PP 1-8:2010